A Climate of Justice: An Ethical Foundation for Environmentalism - Brown, Marvin T.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This open access book helps readers combine history, politics, and ethics to address the most pressing problem facing the world today: environmental survival. In A Climate of Justice, Marvin Brown connects the environmental crisis to basic questions of economic, social, and racial justice. Brown shows how our current social climate maintains systemic injustices, and he uncovers resources for change through a civic ethics of repair and reciprocity. A must-read for researchers and educators in the area of environmental ethics and those teaching courses in the fields of public policy and environmental sustainability. With the support of more than 30 libraries, the LYRASIS United Nations Sustainable Development Goals Fund has enabled this publication related to SDG13 (Climate Action) to be available fully open access. .
Preface -- Chapter 1 Introduction: Three Kinds of Engagement -- Part 1: The Interpretive Framework -- Chapter 2 The Earth -- Chapter 3 Our Humanity -- Chapter 4 The Social -- Chapter 5 The Civic -- Part 2: Telling (3z(BTelling(3y (BStories -- Chapter 6 White Compromises and American Prosperity -- Chapter 7 Einhold Niebuhr during the Time of the White Compromise -- Chapter 8 The Sharecropper$1 (Bs Story and an Ethics for Environmentalism -- Part 3: Empowering the Civic -- Chapter 9 Civilian Empowerment: A Theological Inquiry -- Chapter 10 The Citizen$1 (Bs Role in Creating a Climate of Justice -- Chapter 11 An Invitation to Civic Dialogue -- Index.s
Keywords: Political science$1 (BPhilosophy.s; Ethics; Social sciences$1 (BPhilosophy.s; Philosophy of nature; Political Philosophy; Moral Philosophy and Applied Ethics; Social Philosophy; Philosophy of Nature